Effect of heat-clearing and detoxifying Chinese medicines combined with conventional therapy on mild hand, foot, and mouth disease with fever: An individual patient data meta-analysis. Issue 23 (5th June 2020) - Yan, Shiyan; Lu, Ying; Zhang, Guoliang; Li, Xiuhui; Wang, Zhong; Yao, Chen; Wu, Guiyun; Luo, Lin; Ai, Yanke; Guo, Zhongning; Li, Hongjiao; Li, Tao; et al.
Abstract: Background: In China, heat-clearing and detoxifying Chinese medicines combined with conventional therapy are commonly applied to treat the mild hand, foot, and mouth disease (HFMD). However, there is lack of solid evidence on the efficacy and safety of such therapies. Methods: We conducted a pooled analysis with individual patient data from 5 strictly randomized controlled clinical trials to assess the efficacy and safety of this combination therapy for mild HFMD. An intention-to-treat analysis was performed. A 2-stage meta-analysis method was adopted to analyze the pooled effect size. Results: In total, 947 patients were included. Compared with conventional therapy, the combination therapy significantly reduced the progression rate of HFMD from mild to severe (odds ratio [OR] 0.43, 95% confidence interval [CI]: 0.22 to 0.83, P  = .01). Meanwhile, the healing time of skin rash and oral ulcer in the combination therapy group was significantly shorter than that of conventional therapy. The overall hazard ratio (HR) of healing time of the skin rash or oral ulcer was 1.22 (95%CI: 1.04 to 1.43; P  = .02). However, except Jinlianqingre effervescent tablets, the combination therapy cannot shorten the time to fever resolution (HR 1.12, 95%CI: 0.97 to 1.29, P  = .14). Because of the heterogeneity, Jinlianqingre effervescent tablets were analyzed separately and the HRs of the time to fever resolution and the healing time of skin rash or oral ulcer were 3.88 (95%CI: 3.19 to 4.72; P  < .0001) and 3.79 (95%CI: 2.81 to 5.11; P  < .0001), respectively. There were 30 adverse events reported in total; 2 cases were related to Chinese medicines. Conclusion: In conclusion, the heat-clearing and detoxifying Chinese medicines on top of conventional therapy can effectively reduce the progressive rate of mild HFMD and improve healing of skin and oral mucosal lesions. More studies are needed for the time to fever resolution.